The interphase period “germination–heading” of 8x and 6x triticale with different dominant Vrn genes - P. I. Stepochkin; A. I. Stasyuk (Вавиловский журнал генетики и селекции)
The existing spring forms of wheat-rye amphiploids are characterized by late maturity due to the long duration of the interphase period “germination–heading”. The manifestation of this trait is influenced by Vrn-1 genes. Their dominant alleles also determine the spring type of development. The results of studying the interphase period “germination–heading” of spring octaploid and hexaploid forms of triticale created for use in research and breeding programs under the conditions of forest-steppe of Western Siberia are given in this article. The interphase period of the primary forms 8xVrnA1, 8xVrnB1 and 8xVrnD1 obtained by artificial doubling of the chromosome number of the wheat-rye hybrids made by pollination of three lines of the soft wheat ‘Triple Dirk’ – donors of different dominant Vrn-1 genes – by a winter rye variety ‘Korotkostebel’naya 69’ was determined under the field conditions in the nursery of octaploid (8x) triticale. In the nursery of hexaploid triticale, this trait was studied in the populations of hybrids obtained by hybridization of these three primary forms of octaploid triticale with the hexaploid winter triticale variety ‘Sears 57’. In the offspring of crossing 8хVrnD1× ‘Sears 57’, spring genotypes of 6x triticale bearing Vrn-D1 were selected. This fact was determined by PСR. It means that the genetic material from the chromosome of the fifth homeologous group of the D genome of the bread wheat is included in the plant genotypes. This genome is absent in the winter 6x triticale ‘Sears 57’. The grain content of spikes of the created hexaploid forms of triticale is superiour to that of the maternal octaploid triticale forms. It was shown that plants of the hybrid populations 8xVrnA1× ‘Sears 57’ and 8xVrnD1× ‘Sears 57’ carrying the dominant alleles Vrn-A1a and Vrn-D1a, respectively, have a shorter duration of the “germination–heading” interphase period than the initial parental forms of primary 8x triticale. The short interphase period of “germination–heading” of the 6x triticale is a valuable breading trait for the creation of early maturing and productive genotypes of triticale.